An investigation of enzyme mechanisms using substrate analogues - Potter, B (1980)
﻿ The synthesis of several fluorinated analogues of thiamine and precursors has been undertaken, all of which exhibit weak activity against E.Coli. A route to 3-fluoro-(R)-alanine has been explored. The first synthesis of the enantiomeric fluorosuccinic acids has been accomplished, and a stereochemical analysis has shown that synthesis via esterified malate precursors using diethylamino- sulphurtrifluoride gives inversion of configuration, whereas prep- aration via aspartic acid and polyhydrogen fluoride in pyridine gives retention of configuration. The circular dichroism spectra of the fluorosuccinic acids are anomalous, being the first example of such behaviour in a-substituted carboxylic acids and derivatives. A previously assigned configuration of a Pseudomonal metabolite ( + )- fluorosuccinic acid has been corrected. The fluorosuccinic acids are not substrates for malic enzyme, but are potent inhibitors of fumarase. Using (2S)-fluorosuccinic acid as a mechanistic probe the fumarase reaction is identified as a bimolecular E2 elimination. A stereochemical analysis of enzymic phosphoryl transfer reactions using CD spectroscopy has been investigated, and a new synthesis of inorganic pyrophosphate used to prepare P1=[(S)- 160, 170, 180]-pyrophosphate whose 31P n.m.r. spectrum is discussed. The first example of 31 p- 17 o coupling as observed by 31 P n.m.r. is demonstrated.- The magnitude of the 31P- 180 isotope shift is dependent on the nature of the phosphorus to oxygen bond. An elegant method for establishing the isotopic configuration of oxygen chiral phosphates by n.m.r. has been developed, requiring the synthesis of D-glucose-6[(S) - 160, 170, 180]-phosphate, adenosine-5'- [(S)- 160, 170, 180]-phosphate, and their six membered cyclic phosphate triesters. Chemical cyclisation of these molecules occurs both with racemisation and inversion of configuration at phosphorus. The chemical synthesis of adenosine-5'[ (S) - 160, 170, 180]- triphosphate has been achieved and exploited to demonstrate that hexokinase phosphoryl transfer proceeds with inversion of config- uration at phosphorus. Pyruvate kinase phosphoryl transfer from 2 [(S)- 160, 170, 180]-phospho- (R)-glycerate also proceeds with inversion of configuration, as does phosphofructokinase phosphoryl transfer from sn-glycerol-3[ (5)- 160, 170, 180]-phosphate.